Pengaruh Kecepatan, Kelentukan, dan Kelincahan Terhadap Kemampuan Dribbling Pemain Futsal - Rahmat Hidayat; Ridho Bahtra; Alnedral Alnedral; Aldo Naza Putra (Departemen Kesehatan Dan Rekreasi Fakultas Ilmu Keolahragaan Universitas Negeri Padang, 2026)
Dribbling ability is one of the techniques that futsal players must have. The small field area requires players to have good dribbling skills in attacking, both when passing opponents and accelerating into the opponent's defense area. This study was conducted to determine the effect of speed, flexibility, and agility on dribbling ability. This type of research is quantitative research using the path analysis method. The population in this study was 25 Vamos Futsal Academy players. The sampling technique used a purposive sampling technique, resulting in a sample of 16 people. The instruments used in this study were 1) a 20-meter speed test, to measure speed, 2) a Sit and Reach Test, to measure flexibility, 3) a Zig-zag Run Test, to measure agility, and 4) a Slalom Dribbling Test, to measure a player's dribbling ability. The test results were analyzed using path analysis techniques to determine the pattern of relationships between variables. Data analysis includes several stages, namely: Data description, Normality test, and Linearity test. Path analysis was conducted to identify the extent of influence of the independent variables on the dependent variable. The results showed that speed, flexibility, and agility contributed 95.3% to dribbling ability. Meanwhile, 4.7% was influenced by other variables not included in this study. Therefore, it can be concluded that speed, flexibility, and agility are important factors that directly influence the dribbling ability of futsal players.